AXIOLOGICAL FOUNDATIONS OF GENDER EQUALITY: CONTEMPORARY SOCIO-PHILOSOPHICAL APPROACHES - Ganiyeva, Malikakhon Sodiqjonovna (Oriental Journal of History, Politics and Law, 2026)
This article examines the axiological foundations of gender equality from the perspective of contemporary social philosophy. Gender equality is interpreted as a fundamental value ensuring human rights, social justice, individual freedom, equal opportunities, and human dignity. Through a comparative analysis of classical and modern philosophical theories, the study explores the place of gender equality within the system of social values and its relationship with social stability, civil society, and sustainable development. The paper also analyzes international approaches and recent reforms implemented in Uzbekistan. It argues that gender equality should be regarded not merely as a legal or political principle but as an essential value underpinning social cohesion and democratic development.